DEVELOPMENT OF HOTS-BASED BIOLOGY SUMMATIVE TEST INSTRUMENT AT ODD SEMESTER OF CLASS XI - Ginting, Elsariya Br (Universitas Negeri Medan, 2024)
This research aims to determined the feasibility of HOTS-based biology summative test instruments from the aspects of validity, reliability, difficulty index, discriminating index, and distractor function. This research was designed using ADDIE development model. The test instrument was validated by experts and undergo three times trial. Research results showed that the test instrument was declared very feasible according to material expert and evaluation expert. Three times trial of multiple-choice question showed: (1) increased trend of validity (respectively 85%, 95%, 100%), (2) increased trend of reliability (respectively 0.72, 0.75, 0.77) with high category, (3) the difficulty index is dominated by medium levels and nearly approached the balanced proportion, (4) the discriminating index are dominated by good category items, and (5) the distractors are effectively functioning. While three times trial of essay question showed: (1) increased trend of validity (respectively 80%, 100%, 100%), (2) decreased trend of reliability (respectively 0.71, 0.71, 0.64) with enough category, (3) the difficulty index is dominated by medium levels but it was still far from the balanced proportion, and (4) the discriminating index are dominated by good category items. It can be concluded that the HOTS-based test instrument is feasible to be use as an evaluation instrument.